2018
DOI: 10.17116/neiro201882481
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of VPS in the early postoperative period following removal of posterior cranial fossa tumors in children

Abstract: At present, the risk of persistent hydrocephalus in children after removal of PCF tumors is lower than that reported in the literature. In our study, it was 8.4%. The age of children under 3 years and repeated operations do not statistically significantly increase the risk of persistent hydrocephalus. Only tumor histology is statistically significant: the highest risk of the need for implantation of VPS was found in the group with anaplastic ependymomas, and the minimal risk was in the group of piloid astrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…According to the outcomes of 117 patients who underwent direct tumor resection in this study, the recurrence rate of hydrocephalus was as high as 20.5%, and the shortest duration was only 7 days. A retrospective study in 2018 found that the recurrence rate after direct resection of tumors in midline regions, such as posterior fossa tumors, in children was 8.4% [3], and this rate was even over 25% in other reports [21] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…According to the outcomes of 117 patients who underwent direct tumor resection in this study, the recurrence rate of hydrocephalus was as high as 20.5%, and the shortest duration was only 7 days. A retrospective study in 2018 found that the recurrence rate after direct resection of tumors in midline regions, such as posterior fossa tumors, in children was 8.4% [3], and this rate was even over 25% in other reports [21] .…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported in the literature that intraventricular hemorrhage is the most common cause of acquired hydrocephalus in infants, including premature babies. After this period, tumors become the most frequent etiology of acquired hydrocephalus, especially midline tumors in the fourth ventricle [2,3,10]. These tumors obstruct the CSF circulation, leading to acquired hydrocephalus, and therefore, this condition is classi ed as obstructive hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
“…In children with brainstem or posterior fossa gliomas, 80-90% have been reported to develop hydrocephalus [17,18]. In adults, the incidence of CH following surgery appears to be lower than 10% in GBM [15,16,[19][20][21]. For lower-grade gliomas, this has not been established, and it is unclear whether the risk for postoperative CH in glioma patients is related to the WHO grade.…”
Section: Introductionmentioning
confidence: 99%
“…In adults, the incidence of CH following GBM resection appears to be lower than 10% ( 16 , 17 , 19 , 20 ). Reported risk factors are ventricular opening during tumor resection ( 16 ), leptomeningeal tumor spread ( 17 ), and the number of pre-shunt craniotomies ( 21 ).…”
Section: Introductionmentioning
confidence: 99%